Effects of cognitive behavioural therapy on insomnia in adults with tinnitus: Systematic review and meta-analysis of randomised controlled trials. (April 2021) - Curtis, Ffion; Laparidou, Despina; Bridle, Chris; Law, Graham R.; Durrant, Simon; Rodriguez, Alina; Pierzycki, Robert H.; Siriwardena, Aloysius N.
Summary: Insomnia is common in patients with tinnitus and negatively affects tinnitus symptoms and quality of life. This systematic review aimed to synthesise evidence of the effectiveness of cognitive behavioural therapy (CBT) based interventions on insomnia in adults with tinnitus. We conducted a comprehensive database search (MEDLINE, CINAHL, Web of Science, CENTRAL, ClinicalTrials.gov and PROSPERO) for published, unpublished and ongoing randomised controlled trials of CBT in adults with tinnitus. Five trials met the inclusion criteria for the systematic review, with four of these providing data for the meta-analysis. This demonstrated a statistically significant reduction in Insomnia Severity Index (a standard diagnostic questionnaire of insomnia used in clinical settings) following CBT (−3.28, 95% CI -4.51,  −2.05, P=<0.001). There was no evidence of statistical heterogeneity (I 2  = 0%). Risk of bias was considered low in all categories except blinding of participants, personnel, and/or the assessment of outcomes. Here, for the first time, we demonstrate that CBT-based interventions can significantly improve sleep in adults with tinnitus.